Analysis of sleep disorders and their influencing factors in patients with ankylosing spondylitis - Xihong Ying; Qiuyan Zhao; Yi Wu; Shasha Deng; Qing Ma; Ronghua Fang (PLoS ONE, 2025)
Objectives Sleep disorders are a common symptom in Ankylosing Spondylitis (AS) patients. In this cross-sectional study, we aimed to understand the current status of sleep disorders in AS patients and to analyze potential factors influencing sleep disorders. Methods A total of 205 AS patients were recruited in the survey. The content included the self-designed demographic data questionnaire, The MOS 36-Item Short Form Health Survey (SF-36), Visual Analogue Scale (VAS), Multidimensional Fatigue Inventory (MF-20), Self-Rating Anxiety and Depression Scale, Pittsburgh Sleep Quality Index questionnaire (PSQI), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index (BASFI) and Bath Ankylosing Spondylitis Metrology Index (BASMI). These data were analyzed using chi-square test, independent sample t-test, Mann-Whitney U test, Pearson correlation analysis, single-factor linear regression analysis, and multiple linear stepwise regression analysis. Results The results showed that the average sleep total score was 8.82 ± 4.146, and the prevalence of sleep disorders was approximately 66.8% in AS patients. Age (F = 29.710, P < 0.001), disease duration (F = 13.025, P < 0.001), anxiety (F = 36.060, P < 0.001), depression (F = 11.808, P < 0.001), and quality of life (t = 6.665, P < 0.001) significantly impacted the sleep total score. Pearson correlation analysis revealed a significant negative correlation between SF-36 total score and sleep total score (r = ‒0.449, P < 0.01), while positive correlations were observed for VAS score, fatigue, anxiety, depression, BASDAI, BASFI, BASMI, age, and disease duration (all P < 0.01). Multivariate analysis showed that age, disease duration, nocturnal pain VAS score, total back pain VAS score, peripheral joint pain VAS score, total fatigue score, total anxiety score, and BASMI total score significantly predicted sleep total score (R² = 0.755, F = 45.334, P < 0.001). Conclusion These findings suggest that medical professionals should pay increased attention to the observed associations between sleep disorders and clinical factors in AS patients, and consider implementing targeted interventions to address sleep-related issues.